BREAST FEEDING AND WEANING PRACTICES IN RURAL AREAS: ITS RELATION TO MALNUTRITION IN CHILDREN LESS THAN ONE YEAR OF AGE - Adeen Akram; Muhammad Saleem Channarh; Ahsan Ahmad (Journal of University Medical & Dental College, 2016)
Abstract: Objective: The objective of this study is to see the current breast feeding and weaning practices in our rural areas and its impact on the growth of children less than one year of age. Design: It is an observational descriptive study. Place and duration of study: Madinah Teaching Hospital University Medical and Dental College Faisalabad from June to September 2015. Patients and Methods: A total of 300 children belonging to rural areas were included in the study. The address was noted from the CNIC of father/mother/caregiver. Only children < 1 year of age belonging to rural areas were included in the study. Infants having chronic illnesses like congenital heart disease, Asthma, Tuberculosis, cystic fibrosis, immunodeficiency or congenital defects like cleft palate and lip were excluded from the study. The weight of each infant was recorded and Classified according to gomezs classification for malnutrition on a predesigned proforma. The data was assessed by using SPSS version 19. Results: Out of 300 infants 121 were on exclusive breast feeding, 81 were on predominant breast feeding and 98 were not being given breast milk. Early ablactation was also observed, at the age of>8-12 months 36 children were not being given breast milk. Weaning foods were started in 152 infants only. The infants who were not being given breast milk were the worst affected group by malnutrition, 37 infants had 3rd degree malnutrition similarly the infants who were not given weaning foods were also affected adversely by malnutrition , 40 infants had 3rd degree malnutrition as compared to 17 who were being given weaning foods. Conclusion: The breast feeding practices in our rural areas are not optimal, the timing and quality of weaning foods are also not appropriate. There is a significant association between breast feeding and weaning patterns with malnutrition in infants less than 12 months of age.